Use of surgical glue versus suture to repair perineal tears: a randomised controlled trial - Adriana Caroci-Becker; Wesllanny Sousa Brunelli; Marlise de Oliveira Pimentel Lima; Angela Megumi Ochiai; Sheila Guimarães Oliveira; Maria Luiza Riesco (BMC, 2023)
Abstract Background Surgical glue has been used in several body tissues, including perineal repair, and can benefit women. Objectives To evaluate the effectiveness of n-butyl-2-cyanoacrylate surgical glue compared to the polyglactin 910 suture in repairing first- and second-degree perineal tears and episiotomy in vaginal births. Design A parallel randomised controlled open trial. Setting Birth centre in Itapecerica da Serra, São Paulo, Brazil. Participants and methods The participants were 140 postpartum women allocated into four groups: two experimental groups repaired with surgical glue (n = 35 women with a first-degree tear; n = 35 women with a second-degree tear or episiotomy); two control groups sutured with thread (n = 35 women with a first-degree tear; n = 35 women with a second-degree tear or episiotomy). The outcomes were perineal pain and the healing process. Data collection was conducted in six stages: (1) up to 2 h after perineal repair; (2) from 12 to 24 h postpartum; (3) from 36 to 48 h; (4) from 10 to 20 days; (5) from 50 to 70 days; and (6) from 6 to 8 months. ANOVA, Student's t, Monte Carlo, x-square and Wald tests were used for the statistical analysis. Results One hundred forty women participated in the first three stages, 110 in stage 4, 122 in stage 5, and 54 in stage 6. The women treated with surgical glue had less perineal pain (p ≤ 0.001). There was no difference in the healing process, but the CG obtained a better result in the coaptation item (p ≤ 0.001). Conclusions Perineal repair with surgical glue has low pain intensity and results in a healing process similar to suture threads. Trial registration Brazilian Registry of Clinical Trials (UTN code: U1111-1184-2507; RBR-2q5wy8o); date of registration 01/25/2018; www.ensaiosclinicos.gov.br/rg/RBR-2q5wy8/